The Rise of Transnational Financial Crimes and Tropical Deforestation - Yacouba Kassouri (Environmental and Resource Economics, 2024)
This paper investigates the impact of trade-related illicit financial flows (IFFs) on tropical deforestation. To adjust for pre-exposure differences in deforestation rates between countries exposed to IFFs and their counterfactuals,~this study adopts propensity score matching and doubly robust weighted regression estimators. The results suggest substantial increases in forest loss in countries exposed to large IFFs. Specifically, the treated countries exposed to IFFs experience an annual increase in forest loss of approximately 10,344.167 hectares compared to their counterfactual controls. This finding~ is largely driven by macro-financial instability resulting from real currency depreciation and tax revenue losses due~ to illicit financial outflows. ~The results highlight the merit of capital controls and state ownership of assets in mitigating the impact of exposure to IFFs on forest loss.
Keywords: F2; F4; O13; 330; Illicit financial flows; Deforestation; Forest cover loss; Tropical countries